Performance Evaluation of Stock Using Markowitz and Sharpe Single Index Model - Gupta, Nishu (International Journal of Psychosocial Rehabilitation, 2020)
Stock Selection since the ages has been a tedious task to perform because that entail lot of analysis. An investor always found a problem in selecting a good stock among various stock available in the market. They always tried to have risk return trade off by investing in different stocks. But they can reduce the unsystematic risk through diversification but what about the systematic risk. Systematic risk is the risk that can be measure but can’t reduce through diversification. For an individual investor it is not possible to calculate the risk of each security. This study helps an investor in constructing an optimal portfolio. For constructing the optimal portfolio two studies has been taken into consideration i.e. Markowitz Model and Sharpe- Single Index Model. After construction of portfolio with the respective models, the performance of the model is compared.